2019
DOI: 10.1016/j.jde.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Willmore flow of planar networks

Abstract: Geometric gradient flows for elastic energies of Willmore type play an important role in mathematics and in many applications. The evolution of elastic curves has been studied in detail both for closed as well as for open curves. Although elastic flows for networks also have many interesting features, they have not been studied so far from the point of view of mathematical analysis. So far it was not even clear what are appropriate boundary conditions at junctions. In this paper we give a well-posedness result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…If p = 2, noting that θ i ss N i = (∂ s κ i )N i = ∇ s κ i we see that a stationary network satisfies the natural boundary conditions at the triple junctions derived for the L 2 -gradient flow of elastic networks in [8,15,14].…”
Section: Remark 22 (Relation Between Classical Formulation and θ-Formentioning
confidence: 87%
“…If p = 2, noting that θ i ss N i = (∂ s κ i )N i = ∇ s κ i we see that a stationary network satisfies the natural boundary conditions at the triple junctions derived for the L 2 -gradient flow of elastic networks in [8,15,14].…”
Section: Remark 22 (Relation Between Classical Formulation and θ-Formentioning
confidence: 87%
“…For the proof see [23,Lemma 3.31]. Moreover by inspecting the proof of Theorem 3.32 in [23] we see that the following holds.…”
Section: N} Is An Admissible Initial Networkmentioning
confidence: 88%
“…[40] [ 40] [ 40,41] Open curves, clamped b.c. [52] [ 29] [ 18,41] Non compact curves [40] [ 40] Networks [15,22,23] [ 14,22] [ 14] We refer also to the two recent PhD theses [38,48]. The aim of this expository paper is to arrange (most of) this material in a unitary form, proving in full detail the results for the elastic flow of closed curves and underlying the differences with the other cases.…”
Section: Asymptotic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for which we got interested in this problem is a previous study of its dynamical counterpart (see [13,14]). The study of the static problem has often revealed to be useful for the analysis of the asymptotic behavior of the solutions of the associated gradient flow and of the singularities that can appear during the evolution.…”
Section: Introductionmentioning
confidence: 99%